2020
DOI: 10.1108/jeee-08-2019-0116
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing antecedents affecting the organizational performance of start-up businesses

Abstract: Purpose The purpose of this paper is to depict the effects and relative importance of technological, organizational, environmental and managerial factors on the organizational performance of start-up businesses. Design/methodology/approach This research’s primary data was collected from 389 start-up companies in Malaysia. Principle component analysis and the orthogonal model with Varimax rotation method are used to perform exploratory factor analysis test. Structural equation modelling is also used in confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
1
11
0
1
Order By: Relevance
“…Indeed, there are very limited studies that applied a real‐world case for BIC performance measurement. Authors including (Barbero et al, 2012; Hasani & O'Reilly, 2020; Torun et al, 2018) propose that although challenging, there is a significant need to assess performance in order to improve incubator policy. In order to fill the gap, in this research, a comprehensive framework for BIC performance measurement using FAHP and FIS was developed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are very limited studies that applied a real‐world case for BIC performance measurement. Authors including (Barbero et al, 2012; Hasani & O'Reilly, 2020; Torun et al, 2018) propose that although challenging, there is a significant need to assess performance in order to improve incubator policy. In order to fill the gap, in this research, a comprehensive framework for BIC performance measurement using FAHP and FIS was developed.…”
Section: Discussionmentioning
confidence: 99%
“…According to the data collection, it can be observed that the resources used in the incubation process are offered and appropriated by the incubators and the startup, respectively. Corroborating the findings about the categories and the importance of resources in the literature (Bergek and Norrman, 2008; Grimaldi and Grandi, 2003; Hasani and O'Reilly, 2020; Hillemane et al. , 2019; McAdam and McAdam, 2008; Somsuk and Laosirihongthong, 2014).…”
Section: Discussion and Analysismentioning
confidence: 99%
“…TBIs are organizations that aim to encourage the development of technology startups (Hillemane et al, 2019), increasing their chances of survival in the market and promoting entrepreneurship and economic development (Bala Subrahmanya, 2017;Bergek and Norrman, 2008;Mian et al, 2016;Roundy and Bayer, 2019), offer a wide range of resources for incubated companies such as physical facilities and infrastructure, administrative services, access to a support network, management orientation and easy access to capital, allowing for the development and continuity of these companies (Bøllingtoft, 2012;Hasani and O'Reilly, 2020;Hillemane et al, 2019;McAdam and McAdam, 2008;Somsuk and Laosirihongthong, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As far as it is known, this paper is the first to investigate the impact of individuals’ well-being on the probability of becoming an entrepreneur from countries with emerging economies as a background. Within the past two decades, entrepreneurship research has mainly addressed firm performance as the most studied dependent variable (Hasani and O’Reilly, 2020; Wiklund et al , 2019); however, from an individual-level of analysis, SWB as an outcome variable has recently attracted the attention of multiple manuscripts (Dijkhuizen et al , 2018; Hmieleski and Sheppard, 2019; Nikolaev et al , 2019). The essence of the argument behind considering entrepreneurship as an antecedent of SWB lies in the consistency between internal desires and actions; in other words, entrepreneurs report a match between motivations and outward activities (Carree and Verheul, 2012).…”
Section: Discussionmentioning
confidence: 99%